Design and validation of the general scale of academic engagement for Spanish adolescents (CAADE) - Begoña María Tortosa Martínez; María del Carmen Pérez-Fuentes (Heliyon, 2024)
Academic engagement is considered one of the most essential elements to achieve educational success and decrease levels of school dropout. However, there is a need to develop reliable, practical and valid instruments that evaluate the academic engagement of adolescents taking into account their multidimensionality. The main aim of this research was to design and validate the General Scale of Academic Engagement for Spanish Adolescents that overcomes this limitation. The elaboration process began with the creation of items that are relying on the evaluation of existing literature, then the items were refined thanks to the reviews of the experts and discussion groups with adolescents. Data from 1158 students in compulsory secondary education were analyzed. The instrument's psychometric properties were determined by comprehension validity, analysis of content, reliability and construct validity. An Exploratory Factor Analysis was performed with the first sample (n = 356), while the second sample (n = 802) was used to verify the factor structure identified through Confirmatory Factor Analysis. Evidence of reliability and validity was provided for the instrument using SPSS Version 27 and SPSS AMOS. The results of the analyses resulted in a questionnaire of 17 items grouped into three factors (Cognitive, Affective-Emotional and Behavioral), and confirm that the General Scale of Academic Engagement for Spanish Adolescents (CAADE) has an adequate construct validity and reliability. In summary, this study has resulted in the development of a tool that can be utilized by educators or any institution concerned in evaluating student academic engagement, a construct that does not yet to have consensus.